Beitrag zur Kenntnis der Bionomie von Exoteleia dodecella L. (Lepidoptera: Gelechiidae). - Lemarie, Jaroslav (Contributions to Entomology = Beiträge zur Entomologie, 1959)
Exoteleia dodecella L. is a pest of pine buds showing a tendency towards a mass multiplication in southern Moravia. Adults are on wing from mid June to the 2nd half of July. The female deposits its orange-yellow eggs on pine needles into or on the sheath, on bark below the base of needle or, as an exception, higher on the needles. The young larvae, hatching in about 10 to 14 days after oviposition, make their first mines in the basal third or fourth part of needle closely to its edge above its sheath. Two types of mines have been observed, viz. a "hockey-stick" and a "needle" type. At the end of September the larva migrates to another needle where it hibernates. In the following spring it invades a third needle and, after a period of about eight days, it attacks the buds where it produces a „roof-like" cocoon. From mid May the larva pupates in the spot of its latest sojourn. The pupal stage lasts for 10 to 14 days.